The Secret Garden [Tajná záhrada anglicky] - Burnett, Frances Hodgson, 1849-1924 (Best of children´s classics, 2022)
"I am sure there is Magic in everything, only we have not sense enough to get hold of it and make it do things for us." When orphaned Mary Lennox comes to live at her uncle's great house on the Yorkshire Moors, she finds it full of secrets. The mansion has nearly one hundred rooms, and her uncle keeps himself locked up. And at night, she hears the sound of crying down one of the long corridors.The gardens surrounding the large property are Mary's only escape. Then, Mary discovers a secret garden, surrounded by walls and locked with a missing key. With the help of two unexpected companions, Mary discovers a way inand becomes determined to bring the garden back to life.